2023
DOI: 10.3390/ijms24086896
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Conformational Sampling for Intrinsically Disordered and Ordered Proteins by Variational Autoencoder

Abstract: Intrinsically disordered proteins (IDPs) account for more than 50% of the human proteome and are closely associated with tumors, cardiovascular diseases, and neurodegeneration, which have no fixed three-dimensional structure under physiological conditions. Due to the characteristic of conformational diversity, conventional experimental methods of structural biology, such as NMR, X-ray diffraction, and CryoEM, are unable to capture conformational ensembles. Molecular dynamics (MD) simulation can sample the dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Furthermore, RNNs have excelled at detecting temporal and sequential patterns in data, making them especially suitable for anomaly detection problems in time series [43]. Previous studies on VAEs have revealed their ability to capture the latent structure of high-dimensional data and detect significant deviations in these data [44]. These references support the choice of these algorithms and reinforce their applicability in the context of cybersecurity for critical infrastructure in a smart city [45].…”
Section: Discussionmentioning
confidence: 87%
“…Furthermore, RNNs have excelled at detecting temporal and sequential patterns in data, making them especially suitable for anomaly detection problems in time series [43]. Previous studies on VAEs have revealed their ability to capture the latent structure of high-dimensional data and detect significant deviations in these data [44]. These references support the choice of these algorithms and reinforce their applicability in the context of cybersecurity for critical infrastructure in a smart city [45].…”
Section: Discussionmentioning
confidence: 87%
“…We compared Phanto-IDP with MD and previously developed deep learning models [ 16 , 17 ]. The models’ ability to reconstruct individual conformation in the trajectory was evaluated using average RMSD, which measured the level of fidelity in capturing conformational features and diversity at the conformational level.…”
Section: Resultsmentioning
confidence: 99%
“…Although these approaches do ensure more sufficient sampling, they still cost a lot of computational resources and time. On the other hand, in recent years, several deep learning–based enhanced sampling methods, such as the variational autoencoder (VAE), have been proposed [ 15 , 16 ]. These methods usually train a generative model on existing MD simulation trajectories to efficiently generate novel protein conformations.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to being pretrained on single-state protein structures, certain methods directly learn distributional ensembles from molecular dynamics simulation trajectories, which exhibit strong correlations with our proposed methods 7,61,62 . However, these models often show suboptimal performance when applied to structured proteins, while demonstrating relatively high sample fidelity in handling intrinsically disordered proteins (IDPs), which inherently possess greater flexibility compared to structured proteins 63,64 . All these methods show the promising aspects of deep learning, pretrained and fine-tuning fashion for this biology problems.…”
Section: Discussionmentioning
confidence: 99%